2016
DOI: 10.1111/1753-0407.12412
|View full text |Cite
|
Sign up to set email alerts
|

Crossover design and its application in late‐phase diabetes studies

Abstract: Highlights• Addressed crossover design application and implementation specific to late-phase diabetes studies.• Performed PK/PD simulation and data mining to show that the key issue, carryover effect, in crossover design is not problematic in proper applications even without washout periods.• Showed that crossover design is suitable for many of current diabetes treatments and earlier compounds in development undergoing clinical trials. AbstractCrossover design has been widely used in late-phase clinical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One of the reasons was that we assumed current study might decrease higher-order carryover effects because the second phase is no intervention for six weeks. Previous study suggested that a washout period was often unnecessary for diabetes studies if the second period is long enough to diminish carryover effect [39]. Another reason was that we would like to reduce dropouts and missing data that usually make a larger bias on crossover trials than on parallel group trials [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons was that we assumed current study might decrease higher-order carryover effects because the second phase is no intervention for six weeks. Previous study suggested that a washout period was often unnecessary for diabetes studies if the second period is long enough to diminish carryover effect [39]. Another reason was that we would like to reduce dropouts and missing data that usually make a larger bias on crossover trials than on parallel group trials [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…If used at the start of a trial, a run-in period can help to document a stable baseline state, determine tolerability, assess potential study regime adherence, or wash out any pretrial interventions if needed 444546. A run-in period might also occur at the beginning of any period of an intervention in a trial, if the intervention requires ramping up to the trial’s therapeutic dose.…”
Section: Section 3a: Methods—participants Interventions and Outcomesmentioning
confidence: 99%
“…The included participants were randomly and equally divided into three groups, A, B, and C, with 10 participants in each group, by using the random number method. The crossover study design was adopted for each group to use the three triage systems by randomized sequence to avoid potential bias on the results (Table 1) (11,12).…”
Section: Grouping Methodsmentioning
confidence: 99%